A set of accessible enhancers enables the initial response of breast cancer cells to physiological progestin concentrations. Issue 22 (25th November 2021) - Zaurin, Roser; Ferrari, Roberto; Nacht, Ana Silvina; Carbonell, Jose; Le Dily, Francois; Font-Mateu, Jofre; de Llobet Cucalon, Lara Isabel; Vidal, Enrique; Lioutas, Antonios; Beato, Miguel; Vicent, Guillermo P
Abstract: Here, we report that in T47D breast cancer cells 50 pM progestin is sufficient to activate cell cycle entry and the progesterone gene expression program. At this concentration, equivalent to the progesterone blood levels found around the menopause, progesterone receptor (PR) binds only to 2800 genomic sites, which are accessible to ATAC cleavage prior to hormone exposure. These highly accessible sites (HAs) are surrounded by well-organized nucleosomes and exhibit breast enhancer features, including estrogen receptor alpha (ERα), higher FOXA1 and BRD4 (bromodomain containing 4) occupancy. Although HAs are enriched in RAD21 and CTCF, PR binding is the driving force for the most robust interactions with hormone-regulated genes. HAs show higher frequency of 3D contacts among themselves than with other PR binding sites, indicating colocalization in similar compartments. Gene regulation via HAs is independent of classical coregulators and ATP-activated remodelers, relying mainly on MAP kinase activation that enables PR nuclear engagement. HAs are also preferentially occupied by PR and ERα in breast cancer xenografts derived from MCF-7 cells as well as from patients, indicating their potential usefulness as targets for therapeutic intervention.